The Influence of YouTube and Instagram Influencers on Consumers’ Purchase Intention of Eiger Products - Syanana, Muhamad Fatan Achsin; Astuti, Budi (Universitas KH. Abdul Chalim Mojokerto, 2026)
Influencers are an important element in digital marketing because they are able to introduce products while shaping perceptions that influence purchasing decisions. However, previous studies have focused on industries such as fashion and have not yet linked influencer credibility with parasocial interaction. This study analyzes the influence of YouTube and Instagram influencers on consumer purchase intentions for Eiger products, using Fiersa Besari as the object. Specifically, this study examines the role of parasocial interaction (PSI) between the audience and Fiersa Besari, and perceived influencer credibility in increasing purchase intention. Physical attractiveness, social attractiveness, attitude homophily, and expertise are also examined as elements that strengthen credibility and parasocial interaction. This study uses a quantitative approach with a survey of 200 active followers of Fiersa Besari on YouTube and Instagram. The data is analyzed using SmartPLS-based Structural Equation Modeling (SEM). The results show that all hypotheses are significant. This means that the higher the credibility and emotional bond of the audience with the influencer, the greater the likelihood of purchasing the promoted product. These findings enrich the influencer marketing literature and provide practical insights for companies in selecting the right influencers.